Quantifying selenium deficiency and potential utilisation of urine as a biomarker for large scale selenium and zinc surveys in Malawi - Phiri, Felix Pensulo (2020)
Micronutrient deficiencies (MNDs), also referred to as hidden hunger, are of global concern with over 2 billion people being at risk. Although MNDs, including iodine (I), iron (Fe) and zinc (Zn), are recognised as being of public health concern especially in sub-Saharan Africa (SSA), there is growing interest in the public health importance of selenium (Se) deficiency, an essential micronutrient important for thyroid and antioxidant functions.